Practice Patterns of Left-Sided Double-Lumen Tube: Does it Match Recommendation from Literature – A Single-Centre Observational Pilot Study - Kar, Prachi (Ann Card Anaesth, 2019)
CONTEXT: Choosing appropriate-size double-lumen tube (DLT) has always been a challenge as it depends on existing guidelines based on gender, height, tracheal diameter (TD), or personal experience. However, there are no Indian data to match these recommendations. AIM: To find out whether the size of DLT used correlates with height, weight, TD, or left main stem bronchus diameter (LMBD). We also documented clinical consequences of any of our current practice. SETTING AND DESIGN: Single-center observational pilot study. SUBJECTS AND METHODS: Prospective, observational study of 41 patients requiring one-lung ventilation with left-side DLT. The choice of DLT was entirely on the discretion of anesthesiologist in charge of the case. Data were collected for TD, LMBD, height, weight, age, sex, and amount of air used in the tracheal and bronchial cuff. Any intraoperative complications and difficulty in isolation were also noted. STATISTICAL ANALYSIS: The statistical analysis was done with the National Council of Statistical Software version 11. RESULTS: Average TD and LMBD were 16.5 ± 0.9 and 10.7 ± 0.8 mm for males and 14.2 ± 1.1 and 9.4 ± 1.1 mm for females, respectively. There was a weak correlation between DLT size and height (R(2) = 0.0694), TD (R(2) = 0.3396), and LMBD (R(2) = 0.2382) in the case of males. For females, the correlation between DLT size and height (R(2) = 0.2656), TD (R(2) = 0.5302), and LMBD (R(2) = 0.5003) was slightly better. CONCLUSION: Although there was a weak correlation between DLT size and height, TD, and LMBD, the overall intraoperative outcome and lung isolation were good.